Pirate, Viking, & Scientist - Chapman, Jared (New York ; Little, Brown and Company, 2014)
"A pirate and a Viking fight to become the very best friend of a kid scientist, who meanwhile devises the perfect formula for all three friends to play happily together"--
Keywords: Friendship -- Juvenile fiction; Experiments -- Juvenile fiction; Friendship -- Fiction; Experiments -- Fiction